Naphthalene-2,6-diyl bis(4-methylbenzenesulfonate) - Aleksandra Piontek (IUCrData, 2018)
The complete molecule of the title compound, C24H20O6S2, is generated by a crystallographic inversion centre at the middle of the naphthalene ring system. The dihedral angle between the naphthalene ring system and the pendant benzene ring is 10.23 (6)° and the C—S—O—C torsion angle is −172.05 (10)°. In the crystal, weak C—H...O interactions link the molecules into (10\overline{1}) sheets.